2014
DOI: 10.1038/tpj.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of warfarin in a paediatric population: time in therapeutic range, initial and stable dosing and adverse effects

Abstract: Warfarin is used in paediatric populations, but dosing algorithms incorporating pharmacogenetic data have not been developed for children. Previous studies have produced estimates of the effect of polymorphisms in CYP2C9 and VKORC1 on stable warfarin dosing, but data on time in therapeutic range, initial dosing and adverse effects are limited. Participants (n=97) were recruited, and routine clinical data and salivary DNA samples were collected from all participants, and analysed for CYP2C9*2, *3 and VKORC1-163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…Several studies of the pharmacogenetics of the response to vitamin K antagonists in children have been published since 2010 and consistently have reported that children with vitamin K oxidoreductase complex 1 (VKORC1) ‐1639AA genotypes require significantly lower doses of warfarin to achieve the same target INR as children with VKORC1 ‐1639GG genotypes, similar to the results of adult studies . However, what is highly inconsistent among the pediatric studies is the relative importance of genetic (primarily VKORC1 and CYP2C9 genotype) and nongenetic/”developmental” factors as determinants of variability in the warfarin dose required to achieve a stable target INR.…”
Section: Warfarin Case Studymentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies of the pharmacogenetics of the response to vitamin K antagonists in children have been published since 2010 and consistently have reported that children with vitamin K oxidoreductase complex 1 (VKORC1) ‐1639AA genotypes require significantly lower doses of warfarin to achieve the same target INR as children with VKORC1 ‐1639GG genotypes, similar to the results of adult studies . However, what is highly inconsistent among the pediatric studies is the relative importance of genetic (primarily VKORC1 and CYP2C9 genotype) and nongenetic/”developmental” factors as determinants of variability in the warfarin dose required to achieve a stable target INR.…”
Section: Warfarin Case Studymentioning
confidence: 97%
“…For example, in the first pediatric study, age accounted for 28.3% of dose variability, and genetic factors contributed ~4% (3.7% for VKORC1 and 0.4% for CYP2C9). In six subsequent studies, the genetic contribution (predominantly VKORC1 genotype) was much larger, accounting for 11.9–52% of dose variability, but in four of these the contribution of age, height, and weight as surrogates for the “developmental” component (29.2–52.8% of dose variability) exceeded the genetic contribution (11.9–21.1%) . Noteworthy are the various ways that “dose” was expressed in the statistical analyses: uncorrected (mg), corrected for weight (mg/kg) or transformed for normalization (mg1/2, (mg/kg)1/2, and log(mg/kg)).…”
Section: Warfarin Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“… investigated the possible impact of patient deconditioning and vitamin K intake or fasting upon the INR response to warfarin. Since 2010, 13 original studies and two meta‐analyses focused on warfarin pharmacogenomics have been published, and these were identified with this search strategy. Data synthesis of these studies confirms that the identified vitamin K epoxide reductase complex subunit 1 ( VKORC1 ) and cytochrome P450 2CP ( CYP2CP ) variants probably contribute to a reduction in warfarin dosing requirements as compared with wild‐type alleles; however, all studies were conducted in patients with warfarin steady states, and most studies had small cohorts with limited ethnic diversity.…”
Section: Anticoagulant Therapy: Which Agent Intensity and Duration?mentioning
confidence: 99%
“…While warfarin treatment accounts for 10% of all adverse drug reaction (ADR) admissions in adults in the UK, in pediatrics it is a very uncommon cause of ADRs. 13 There have been seven pharmacogenetic studies of warfarin in children [14][15][16][17][18][19][20] (Table 1). Due to the heterogeneity in the data reported in studies, a meta-analysis would be difficult to undertake, unless individual patient data were available.…”
Section: Warfarin and New Oral Anticoagulantsmentioning
confidence: 99%